What you did not tell a Russian past and the journey home - Mazower, Mark 1958- (Other Press, 2017)
"In a tribute to his late father, British historian Mark Mazower traces his family's story from the end of the nineteenth century to today, beginning with his grandfather Mordkhel Mazower's birth in the town of Grodno, part of the Pale of Settlement to which the majority of the Russian Empire's Jews were confined. An activist and member of the Communist Bund, Mordkhel--who later assumed the more European name "Max"--Travelled widely in the years surrounding the Revolution before ultimately settling in England, where his son would live his entire life"--
Keywords: Mazower, Mark -- 1958-; Allgemeiner Jüdischer Arbeiterbund in Litauen, Polen und Rußland; Geschichte; Familie; Juden; Ahnen; Mazower, Mark / Family; Historians / England / Biography; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; HISTORY / Jewish; HISTORY / Russia & the Former Soviet Union; Autobiographies; Autobiografie; Biografie